¬¬¬Pemodelan Matematika Penyebaran Penyakit Covid-19 dengan Menggunakan Model SIRS - Maghfira Izzani Afwan; Helma Helma (UNIVERSITAS NEGERI PADANG, 2021)
Abstract — Covid-19 is a collection of viruses that infect the respiratory system and cause death. Covid-19 is transmitted through a liquid splash that is released when an infected individual coughs, sneezes or talks. Prevention of Covid-19 transmission can be done by not making contact with infected people, because there is a possibility that patients who have recovered from Covid-19 will be infected again due to a decreased immune system in the body. The purpose of this study was to determine the form of a mathematical model in the spread of the Covid-19 disease using the SIRS model and interpret the results of the analysis from the mathematical model. The method used is to analyze the conditions related to the problem so that it can be done to form a mathematical model of the spread of the Covid-19 disease. Based on the results of the analysis, the spread of the Covid-19 disease is influenced by the level of transmission due to contact with people infected with Covid-19, the presence of immigrants entering Indonesia from countries infected with the Covid-19 disease and a decreased immune system in people who are infected with Covid-19 has recovered from the Covid-19 disease.Keywords — Mathematical Model, SIRS Model, Covid-19Abstract — Covid-19 is a collection of viruses that infect the respiratory system and cause death. Covid-19 is transmitted through a liquid splash that is released when an infected individual coughs, sneezes or talks. Prevention of Covid-19 transmission can be done by not making contact with infected people, because there is a possibility that patients who have recovered from Covid-19 will be infected again due to a decreased immune system in the body. The purpose of this study was to determine the form of a mathematical model in the spread of the Covid-19 disease using the SIRS model and interpret the results of the analysis from the mathematical model. The method used is to analyze the conditions related to the problem so that it can be done to form a mathematical model of the spread of the Covid-19 disease. Based on the results of the analysis, the spread of the Covid-19 disease is influenced by the level of transmission due to contact with people infected with Covid-19, the presence of immigrants entering Indonesia from countries infected with the Covid-19 disease and a decreased immune system in people who are infected with Covid-19 has recovered from the Covid-19 disease. Keywords — Mathematical Model, SIRS Model, Covid-19